"We Operate as an Organ": Parent Experiences of Having a Child With Type 1 Diabetes in a Rural Area. Issue 1 (February 2023) - Lewis, Laura Foran; Brower, Paige MacDonald; Narkewicz, Sarah
Purpose: The purpose of this study is to explore the experiences of parents of children with type 1 diabetes mellitus (T1DM) who are living in rural areas. Individuals living in rural areas face barriers to accessing health care that lead to significant health disparities with increased morbidity and mortality. There is a need to understand the unique experiences of those living in rural communities to support their health needs. Methods: In this qualitative study, a convenience sample of 11 parents of children who were diagnosed with T1DM in the last 10 years living in Vermont were recruited through connections with local health professionals and family support networks and interviewed about their experiences. Interviews were transcribed verbatim and analyzed using Braun and Clarke's 6-step approach to reflexive thematic analysis. Results: Five themes were identified to capture the experience of parenting a child with T1DM in a rural community, including enduring emotional traumas, living life on call, adapting to everyday challenges, lacking a safety net for support, and finding a rhythm. Conclusions: Although findings echo many themes found in previous studies on experiences of parents of children with T1DM, participants also identified unique barriers such as physical distance from formal and informal support systems, unreliable and/or insufficient technological resources, and lack of understanding of T1DM by their communities, including among child care and schools. Diabetes care and education specialists working with families living in rural areas must explore ways to educate key supports to these families to minimize isolation, stigma, and burnout among parents.